Prensa escrita y los hábitos de la lectura en los adolescentes de la Cooperativa 20 de Febrero, ciudad de Quevedo, año 2019 - Moreira Lima, Danny Andres (2020)
The written press in the city of Quevedo is a fundamental basis to keep Quevedeña citizens informed, from that point lies the importance of encouraging reading in the adolescents of the February 20 cooperative, in order to promote effective development in their intellect and in addition to values and principles. This research project will seek to direct adolescents to generate reading habits, which are of paramount importance for their personal and academic development, since they will provide them with effective reading skills, in addition the local written press will keep them informed of the news happening to local, national and international level, for which strategies focused on the media will be implemented to make their contents more attractive and thus capture the attention of adolescents. The research will be structured in four chapters where the objectives to be achieved will be detailed, the respective theoretical support, in addition to the methodologies that will be applied for data collection, and a fundamental point is the alternative proposal with which a solution will be given to the problematic